Physiotherapy in the Management of Chronic Pain: Insights from Recent Literature - Jasser, Maram Ali; Alshehri, Raw‏an Abdullah Mohammad; Sheikhein, Amani Mohammad; Khawaji, Nouf Fahad; Hakami, Fatimah Mohammad Hussain; Almones, Wejdan Misfer; Mahzari, Jawaher Abdulrahman; Hamam, Hadeel Abdulsalam; Al-Shahrani, Munira Nasser (Journal of Posthumanism, 2024)
Chronic pain is a widespread and debilitating condition that affects millions globally, often resulting in reduced quality of life and significant socioeconomic burden. Physiotherapy has emerged as a cornerstone in the multidisciplinary management of chronic pain, offering a wide range of interventions tailored to individual needs. This review article explores recent literature on the efficacy, mechanisms, and evolving role of physiotherapy in managing chronic pain. It highlights various therapeutic approaches including exercise therapy, manual therapy, electrotherapy, and cognitive-behavioral strategies. Emphasis is placed on evidence-based practices, the integration of physiotherapy within interdisciplinary care models, and emerging innovations in technology-assisted rehabilitation. The findings support the critical role of physiotherapists in not only alleviating symptoms but also addressing the underlying functional and psychological components of chronic pain. Continued research and clinical innovation are vital to optimizing patient outcomes and ensuring holistic, patient-centered care.